Development of Community Participation on Dengue Hemorragic Fever Surveilance and Prevention by Empowerment Process, Dankwean Subdistrict, Chokchai District, Nakhon Ratchasima Province - Phorkrathoke, Matuphum; Satayavongthip, Bhuddhipong (Ratchaphruek Journal, 2014)
This study aimed to develop community participation on Dengue Hemorrhagic Fever surveillance and prevention by Empowerment Process at Dankwean Sub-district, Chokchai District, Nakhon Ratchasima Province. The research was divided into 3 phases: community context study, development process and development process results. Samples were 47 people. They were 3 health officers, 8 community leaders, and36 public health volunteers. Research tools were data record form,observation form, explore data, questionnaire, and guideline for focus group discussion. Data were collected from August to October 2013. Quality data was analyzed by using content analysis and quantitative data was analyzed by mean, percentage and standard deviation. Also, T-test were used for comparison between pre-and post-development process. The result found that Dankwean Sub-district which is 15 kilometers far from the center of Chokchai District, most of villagers produced and sold the pottery. This, the community was the semi-urban society. The majority environment was utensils kiln/pottery leavings. The disease hemorrhagic fever is found and the number of the patient goes up in the community since a pottery shop was a place where the mosquitoes lived. After development process, the research result found that the participating points in the controlling and prevention dengue hemorrhagic fever increased with statistical significant (P<.05). Awareness point in the controlling and prevention dengue hemorrhagic fever also increased with statistical significant (P<.05). In contrast, the house, container and Breteau Indexes were decreased.